2012
DOI: 10.1002/jssc.201101092
|View full text |Cite
|
Sign up to set email alerts
|

Influence of temperature on peak shape and solvent compatibility: Implications for two‐dimensional liquid chromatography

Abstract: Solvent compatibility is a limiting factor for the success of two-dimensional liquid chromatography (2-D LC). In the second dimension, solvent effects can result in overpressures as well as in peak broadening or even distortion. A peak shape study was performed on a one-dimensional high-performance liquid chromatography (HPLC) system to simulate the impact of peak distorting solvent effects on a reversed-phase second dimension separation operated at high temperatures. This study includes changes in injection v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…The magnitude of this solvent strength effect depends strongly on the sample volume. While understanding quantitatively its influence on the dispersion of the analyte is important for the optimization of the chromatographic separation, it is particularly so in the case of comprehensive twodimensional LC where relatively large volume fractions collected from the effluent of the first column are injected in the second column operated with a mobile phase of different composition [50,51].…”
Section: Discussionmentioning
confidence: 99%
“…The magnitude of this solvent strength effect depends strongly on the sample volume. While understanding quantitatively its influence on the dispersion of the analyte is important for the optimization of the chromatographic separation, it is particularly so in the case of comprehensive twodimensional LC where relatively large volume fractions collected from the effluent of the first column are injected in the second column operated with a mobile phase of different composition [50,51].…”
Section: Discussionmentioning
confidence: 99%
“…One option was to collect 303 nL in each 13th D1 fraction (1 min + 31 s of refill time). In order to avoid a solvent strength effect which might significantly affect the analyte’s peak shape and retention time in D2, , it was instead decided to split the larger fraction in two parts. During flow stabilization at 3% B, the last fraction collected prior to each pump refill was flushed to the D2 column.…”
Section: Methodsmentioning
confidence: 99%
“…The RP × RP mode is the mode in the 2D-LC system most frequently used to separate compounds (Iguiniz & Heinisch, 2017). Some previous studies have found that the RP × RP mode provided better mobile phase compatibility than other 2D-LC modes because of compatibility and similar physicochemical properties of the mobile phases used in the heart-cutting 2D-LC system (Haun, Teutenberg, & Schmidt, 2012;Ji et al, 2018).…”
Section: The Selection Of 2d-lc Systemmentioning
confidence: 99%